2014
DOI: 10.1177/1545968314526644
|View full text |Cite
|
Sign up to set email alerts
|

Is the Recovery of Functional Balance and Mobility Accompanied by Physiological Recovery in People With Severe Impairments After Stroke?

Abstract: During stroke rehabilitation, all participants improved functionally. Some patients improved physiologically, though near discharge, all participants remained very impaired. Future studies with larger sample sizes are needed to explore the capacity for physiological recovery in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 33 publications
2
9
0
Order By: Relevance
“…Changes in functional performance (eg, as measured by observational rating scales) can also improve despite little evidence of restoration of the paretic limb's contribution to balance control. 22,38 Therefore, we believe it is essential to differentiate between simple loading asymmetry and asymmetries in limb contribution to balance control to unmask dyscontrol underlying observed patient performance. This kind of specific information allows physiotherapists to determine what aspects of balance control change with intervention, and thus inform new intervention approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in functional performance (eg, as measured by observational rating scales) can also improve despite little evidence of restoration of the paretic limb's contribution to balance control. 22,38 Therefore, we believe it is essential to differentiate between simple loading asymmetry and asymmetries in limb contribution to balance control to unmask dyscontrol underlying observed patient performance. This kind of specific information allows physiotherapists to determine what aspects of balance control change with intervention, and thus inform new intervention approaches.…”
Section: Discussionmentioning
confidence: 99%
“…17 Finally, some individuals post-stroke can improve their BBS scores without any concomitant improvement in physiological measures of standing balance. 18,19 Thus, individuals may achieve ''good'' BBS performance by applying compensatory strategies without recovering from the stroke-related impairments underlying their poor balance. 18 Thus, individuals who achieve a BBS score greater than the age-and gender-matched normal value may still not have normal balance.…”
mentioning
confidence: 99%
“…As well, the outcomes of the review focused on not just physical function but immobility-related poststroke complications, which are known to be higher in the severe stroke population and contribute to high levels of caregiver burden 28–30. In terms of limitations, it has been reported that the defining severe stroke is difficult due to different criteria used to classify severity 79. The use of objective scores on validated outcome measures to classify stroke severity in our systematic review was deemed necessary to ensure that participants had actually sustained a severe stroke.…”
Section: Discussionmentioning
confidence: 99%